Beyond Technology: Investigating the Impact Of Phishing Emails on Human Behavior and Decision-Making in Educational Institutions - Gautam, Bhim Chandra; Jha, Sudan (Nepalese Journal of Management Science and Research, 2025)
Phishing emails remail a persistent and evolving threat, particularly in educational institutions, where sensitive data and intellectual property are frequently targeted. Attackers create successful phishing by exploiting human vulnerabilities by sending out trustworthy-looking emails which leads to severe consequences for educational institutions. Phishing emails are beyond the technical aspects of cybersecurity and more towards cyber awareness of users. Decision making process and responses of staff, faculty and students towards phishing emails sheds to non-technical factors contributing to successful phishing attempts. We identify key psychological triggers and contextual influences that lead to compromised security. This research explores the need for comprehensive strategists and develop the strategy in the context of human behavior for phishing emails which address human behavior in cybersecurity and behavior modification to mitigate the risks of phishing attacks in educational institutional.